2021
DOI: 10.5222/jarss.2021.29484
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Oculocardiac Reflex Incidence In Pediatric Strabismus Surgery: Retrospective Study

Abstract: INTRODUCTION: Oculocardiac reflex (OCR) activation is common during the strabismus surgery. As a result of the OCR, sinus bradycardia, atrioventricular block, ventricular fibrillation and even asystole may occur. Pediatric patients are also more vulnerable to harmful effects of this reflex. The aim of this study was to determine the possible risk factors affecting the incidence of OCR in pediatric patients undergoing strabismus surgery. METHODS: The medical records of the pediatric patients who underwent strab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“… 21 In a recent retrospective logistic regression analysis of strabismus surgery in children, the 37 who received rocuronium were 3.1 times less likely to have 20% OCR than the 49 who did not get neuromuscular blockade. 85 …”
Section: Influence Of Anesthesiologistmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 In a recent retrospective logistic regression analysis of strabismus surgery in children, the 37 who received rocuronium were 3.1 times less likely to have 20% OCR than the 49 who did not get neuromuscular blockade. 85 …”
Section: Influence Of Anesthesiologistmentioning
confidence: 99%
“… 131 Jean et al reviewed regional anesthesia for eyes suggesting that dexmedetomidine “increases local anesthetic potency and prolongs duration of analgesia without an increase in adverse events.” 132 In a retrospective study of strabismus surgery in children, the 34 who received pre-induction IV midazolam were 3.6 times less likely to have 20% OCR than the 52 who did not get it. 85 …”
Section: Influence Of Anesthesiologistmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that increased anesthesia depth in uences subcortical areas and prevent the development of OCR through the suppression of nociceptive and autonomic re exes (9) and that OCR can be prevented by retrobulbar block and with anticholinergic medications (1). Several studies in the literature have investigated the effects of using various anesthetic agents in pediatric strabismus surgery on the incidence of OCR.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of these studies; propofol or remifentanil anesthesia was associated with a higher incidence of OCR compared to sevo urane and des urane when midazolam was used as the induction agent (10); dexamethasone administered as nasal prophylaxis increased the rate of OCR (11); ketamine and midazolam showed similar effects and did not reduce the incidence of OCR (12). On the other hand, not administering neuromuscular blockers and premedication with benzodiazepine have been reported to reduce the risk of OCR by 3.64 and 3.11 times, respectively (9). In addition, atropine premedication has been reported to reduce OCR and prevents undesired effects of dysrhythmias (13).…”
Section: Introductionmentioning
confidence: 99%